Mass spectrometric detection of KRAS protein mutations using molecular imprinting. Issue 48 (2nd December 2021) - Norman, Rachel L.; Singh, Rajinder; Muskett, Frederick W.; Parrott, Emma L.; Rufini, Alessandro; Langridge, James I.; Runau, Franscois; Dennison, Ashley; Shaw, Jacqui A.; Piletska, Elena; Canfarotta, Francesco; Ng, Leong L.; et al.
Abstract : We show using Molecular imprinted Polymers (MIPs) and LC-MS/SRM that we can identify the KRAS mutation in cancer patients plasma as well as carry out epitope discovery for drug target evaluation. Abstract : Cancer is a disease of cellular evolution where single base changes in the genetic code can have significant impact on the translation of proteins and their activity. Thus, in cancer research there is significant interest in methods that can determine mutations and identify the significant binding sites (epitopes) of antibodies to proteins in order to develop novel therapies. Nano molecularly imprinted polymers (nanoMIPs) provide an alternative to antibodies as reagents capable of specifically capturing target molecules depending on their structure. In this study, we used nanoMIPs to capture KRAS, a critical oncogene, to identify mutations which when present are indicative of oncological progress. Herein, coupling nanoMIPs (capture) and liquid chromatography-mass spectrometry (detection), LC-MS has allowed us to investigate mutational assignment and epitope discovery. Specifically, we have shown epitope discovery by generating nanoMIPs to a recombinant KRAS protein and identifying three regions of the protein which have been previously assigned as epitopes using much more time-consuming protocols. The mutation status of the released tryptic peptide was identified by LC-MS following capture of the conserved region of KRAS using nanoMIPS, which were tryptically digested, thus releasing the sequence of a non-conserved (mutated) region. This approach was tested in cell lines where we showed the effective genotyping of a KRAS cell line and in the plasma of cancer patients, thus demonstrating its ability to diagnose precisely the mutational status of a patient. This work provides a clear line-of-sight for the use of nanoMIPs to its translation from research into diagnostic and clinical utility.